Proximity in English and Lithuanian - Šeškauskienė, Inesa (Kalbotyra, 2003)
The article sets out to disclose the semantic structure of the spatial prepositions of proximity by and beside in English and šalia, greta and ties in Lithuanian. The paper argues that proximity covers a wide range of spatial relations. More specifically, the above prepositions refer to different types of spatial organisation: regional and non-regional. The first type covers at least two subtypes of regions: qualitative/functional (by) and geometrical region (ties). Within non-regional spatial organisation, two varieties seem to be relevant: sequence in space (šalia) and rowtype organisation of entities (beside, greta). Cross-linguistically, the prepositions under study in most cases manifest partial overlap of meaning.